Immune biomarker differences and changes comparing HCV mono-infected, HIV/HCV co-infected, and HCV spontaneously cleared patients. - Lauren E Kushner; Aaron M Wendelboe; Laura C Lazzeroni; Aarthi Chary; Mark A Winters; Anu Osinusi; Shyam Kottilil; Michael A Polis; Mark Holodniy (PLoS ONE)
Background Immune biomarkers are implicated in HCV treatment response, fibrosis, and accelerated pathogenesis of comorbidities, though only D-dimer and C-reactive protein have been consistently studied. Few studies have evaluated HIV/HCV co-infection, and little longitudinal data exists describing a broader antiviral cytokine response. Methods Fifty immune biomarkers were analyzed at baseline (BL) and HCV end of treatment follow-up(FU) time point using the Luminex 50-plex assay in plasma samples from 15 HCV-cleared, 24 HCV mono- and 49 HIV/HCV co-infected patients receiving antiretroviral treatment, who either did or did not receive pegylated-interferon/ribavirin HCV treatment. Biomarker levels were compared among spontaneous clearance patients, mono- and co-infected, untreated and HCV-treated, and sustained virologic responders (SVR) and non-responders (NR) at BL and FU using nonparametric analyses. A Bonferroni correction, adjusting for tests of 50 biomarkers, was used to reduce Type I error. Results Compared to HCV patients at BL, HIV/HCV patients had 22 significantly higher and 4 significantly lower biomarker levels, following correction for multiple testing. There were no significantly different BL levels when comparing SVR and NR in mono- or co-infected patients; however, FU levels changed considerably in co-infected patients, with seven becoming significantly higher and eight becoming significantly lower in SVR patients. Longitudinally between BL and FU, 13 markers significantly changed in co-infected SVR patients, while none significantly changed in co-infected NR patients. There were also no significant changes in longitudinal analyses of mono-infected patients achieving SVR or mono-infected and co-infected groups deferring treatment. Conclusions Clear differences exist in pattern and quantity of plasma immune biomarkers among HCV mono-infected, HIV/HCV co-infected, and HCV-cleared patients; and with SVR in co-infected patients treated for HCV. Though >90% of patients were male and co-infected had a larger percentage of African American patients, our findings may have implications for better understanding HCV pathogenesis, treatment outcomes, and future therapeutic targets.